1987
DOI: 10.1128/iai.55.9.2208-2214.1987
|View full text |Cite
|
Sign up to set email alerts
|

Localization of stx, a determinant essential for high-level production of shiga toxin by Shigella dysenteriae serotype 1, near pyrF and generation of stx transposon mutants

Abstract: Hfr strains of Shigella dysenteriae serotype 1 were constructed by transient integration of an RP4 plasmid derivative carrying transposon TnSOI into the Shigella chromosome through TnSOl-mediated cointegration. The Hfr strains were mated with Escherichia coli K-12 recipients carrying various auxotrophic markers, and E. coli recombinants which had received prototrophic Shigella genes were selected. Some of the E. coli transconjugants produced high levels of a cytotoxin which was neutralized by both polyclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Genetic studies have mapped stx near pyrF, a chromosomal locus at 28 min that is not linked to other known virulence determinants of Shigella spp. (Sekizaki et al, 1987). This approximate location was corroborated by studies with chlorate-resistant mutants of S. dysenteriae 1.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Genetic studies have mapped stx near pyrF, a chromosomal locus at 28 min that is not linked to other known virulence determinants of Shigella spp. (Sekizaki et al, 1987). This approximate location was corroborated by studies with chlorate-resistant mutants of S. dysenteriae 1.…”
Section: Introductionmentioning
confidence: 72%
“…In E. coli , this region encompasses ≈ 56 kbp. This location correlates well with prior genetic mapping, which placed the stx operon near pyrF at min 28 and near the trp and putative chl loci at min 27 (Gemski et al ., 1972; Sekizaki et al ., 1987; Neill et al ., 1988).…”
Section: Resultsmentioning
confidence: 99%
“…The B subunit binds to its cell surface receptor, a glycolipid, globotriosyl ceramide (Gb3), carrying a terminal Galoa(1-4)Gal moiety (20,25). Chromosomal sixA and stxB genes which encode the Shiga toxin A and B subunits, respectively, have been mapped, cloned (45,48), and sequenced (48). The role of Shiga toxin in pathogenesis has recently been explored by Fontaine and colleagues (12), who demonstrated that it influences the severity of bacillary dysentery by inducing colonic ischemia and inflation of the polymorphonuclear intestinal compartment during the infection process.…”
mentioning
confidence: 99%